15N‐Labeling of Egg Proteins for Studying Protein Network Formation During Pound Cake Making. Issue 3 (5th December 2016) - Deleu, Lomme J.; Wilderjans, Edith; Van Haesendonck, Ingrid; Brijs, Kristof; Delcour, Jan A.
Abstract : Proteins from wheat and egg are important for pound cake texture, but their exact role is insufficiently understood. A clear, analytical distinction between proteins from wheat flour, egg white, or egg yolk has been a main challenge. However, this can be addressed by using egg proteins carrying 15 N. Therefore, egg white and yolk protein were enriched in 15 N by mixing 15 N‐labeled leucine into hen feed. Incorporation of egg and flour proteins in the protein network was monitored based on changes in their extractability during cake making. The relative contribution of different noncovalent and covalent bonds could be determined by using different extraction media. We for the first time distinguished between the contribution of egg white, egg yolk, and wheat protein in network formation during pound cake making. Our results show that during batter mixing hardly any intermolecular disulfide bonds are formed and that baking induces tremendous changes in protein extractability. A protein network based on both disulfide bonds and hydrophobic interactions is formed during baking. This covalent network includes almost all egg white protein and most of the yolk and wheat flour protein. The remaining protein fraction most probably lacks sulfhydryl groups and/or intramolecular disulfide bonds.